Toxic Leadership and the Organizational Commitment of Senior-Level Corporate Executives - Yaghi, Majed (Journal of Leadership, Accountability and Ethics, 2019)
Senior executives are often the tip of the hierarchal spear with skillset, expertise and business acumen that are incredibly vital to organizations. Naturally, they are expected to display high commitment levels to the organization, especially during tough times, like the reign of a toxic leader. This qualitative study examined the nature of organizational commitment through the prism of seven senior executives and revealed four main themes. Overall, circumstantial organizational changes such as the behavior of board members and chief executives, as well as frequent restructuring greatly influences the commitment of senior executives. Furthermore, those senior executives form a symbiotic relationship with their organizations which guides their commitment and consequential reciprocal behavior.